Synthesis of Nanochitosan from Cambarus Bartonii Waste and its Utilization in The Removal of Polycyclic Aromatic Hydrocarbons in Surface Water from Ifite Ogwari, Southeastern Nigeria - Vincent Okafor; Deborah Kehinde; Abimbola Akinyele; Benjamin Modozie (Nanochemistry Research)
Access to potable water is a global problem, especially in rural communities of the world. Ifite Ogwari is a rural community in Southeastern Nigeria that depends mostly on surface water for its water needs such as drinking. This work explored the use of nanochitosan for removing polycyclic aromatic hydrocarbons (PAHs) contained in the surface water obtained from Ifite Ogwari. Chitosan extracted from Cambarus bartonii waste (CbC) and artificial chitosan (ArC) supplied by ChitoLytic were reduced to nanochitosan particles. The nanochitosan particles were characterized using Dynamic Light Scattering (DLS), also known as Photon Correlation Spectroscopy, Fourier Transformed Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), and X-ray Diffraction (XRD). PAHs were assessed in untreated and treated water samples using Gas Chromatography-Flame ionization Detector (GC-FID). Results of DLS particle size analyzer ranged between 55.78 nm and 92.64 nm. FTIR gave bands at 2922.2 cm−1 and 1405.2 cm−1 representing C–H and C–N groups, respectively, while the band at 1025.0 cm−1 stretches C–O–C groups. SEM results show interconnected microporosity while XRD results demonstrate sharp peaks at 2θ = 8.20o, 32.08 o, 38.00 o and 45.76 o for nanochitosan from Cambarus bartonii waste (CbNC) and 2θ = 20.21 o, 31.63 o and 45.48 o for nanochitosan from artificial chitosan (ArNC). Nine PAHs were detected in the untreated water while seven were below detectable limit but none was detected in the treated water samples. This study indicates that nannochitosan synthesized from C. bartonii waste could be used for the removal of PAHs from contaminated surface water.